No more dead dogs - Korman, Gordon (New York : Scholastic, 2000)
Eighth-grade football hero Wallace Wallace is sentenced to detention attending rehearsals of the school play where, in spite of himself, he becomes wrapped up in the production and begins to suggest changes that improve not only the play but his life as well.
M
610
M
Keywords: Theater -- Fiction; Schools -- Fiction; Football -- Fiction; Humorous stories